Antecedent model of information technology infrastructure flexibility towards agility: Questionnaire evaluation - Hassan, N.H.B. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents a research-in progress which explores the antecedent factor of Information Technology (IT) infrastructure flexibility. The purpose of this paper is to describe the questionnaire evaluation method that is used to measure the relationship of learning orientation, information technology infrastructure flexibility, and organizational agility. Questionnaire evaluation is conducted because this process is one of the critical parts in quantitative research. Although the items for questionnaire were adopted and adapted from validated items, the review from experts is essential due to different research focuses as well as the group of targeted respondents. The questionnaire was reviewed for clarity, wording, content and format. Hence, this paper elaborates on two aspects of questionnaire evaluation method. First, it describes techniques undertaken for the development of questionnaire and expert review. Second, it discusses on the findings of the expert review processes and the adjustment that has been made to the questionnaires. The findings of these expert review processes are beneficial in improving the reliability and validity of questionnaires. The modified questionnaire will later be used in the next stage of this research. Â© 2015 IEEE.